Long-Term Implant Survival After 100 Maxillary Sinus Augmentations Using Plasma Rich in Growth Factors. Issue 2 (April 2017) - Khouly, Ismael; Pardiñas López, Simón; Aliaga, Ignacio; Froum, Stuart J.
Abstract : Purpose: To identify determinants of long-term implant survival after sinus augmentation procedure (SAP) using a combination of plasma rich in growth factors (PRGF) and graft material. Materials and Methods: Patients were included in this retrospective study if they underwent SAP through a lateral wall approach using PRGF in combination with mainly xenograft, and received implants restored for at least 1 year. Sociodemographic, behavioral and implant characteristics (clinical factors, implant details, surgical details, prosthesis details, and complications) were analyzed. Results: Sixty-seven patients received 217 implants in 100 augmented sinuses. The mean follow-up was 7.2 years. Overall, 22 implants failed in 15 patients (90% cumulative implant survival). Multivariable models showed greater implant survival with implants placed with ≥5 mm of residual crestal bone height (RBH) compared with those placed with <3 mm of RBH. There was also an improvement in survival comparing implant lengths. In addition, immediate loading of implants significantly increased the risk of implant failure. Conclusion: The use of PRGFs for maxillary sinus grafting may be an effective and safe treatment option for the rehabilitation of atrophic edentulous posterior maxillae. However, randomized clinical trials are needed to confirm these findings.